Isolation, purification and characterization of extracellular vibriolytic factors from Pseudomonas species. - Dalisay, Doralyn S.
Pseudomonas spp. P. aeruginosa JP4, P. aeruginosa CD2 and P.fluorescens isolated from aquatic environments produce extracellular vibriolytic factors when grown in nutrient broth. Production of vibriolytic factors was noted during the logarithmic phase of bacterial growth. Vibriolytic activity was examined based on the decrease in the optical density of a standard suspension of Vibrio harveyi, causative agent of luminescent vibriosis in shrimp pond and hatchery systems., Five extracellular vibriolytic factors of Pseudomonas aeruginosa JP4 were isolated and partially purified by ammonium sulfate fractionation, followed by a combination of column chromatography with DEAE-Cellulose and gel filtration in Sephadex G-100. The molecular weights of the vibriolytic factors wer estimated to be 27, 90, 98, 120 and 135 kDa by gel filtration column chromatography. Two of the five vibriolytic factors possessed proteolytic activity. This is the first report of vibriolytic factors of Pseudomonas aeruginosa JP4 that possess proteolytic activity at the same time. Vibriolytic activity was optimum at 30 degrees centigrade and pH 7.0. The vibriolytic factors were unstable to heat, and were completely inactivated when exposed to pH<4 and pH>8. The study reveals that Pseudomonas species can possibly exert their probiotic activity by having a battery of vibriolytic factors which target V. harveyi. This provides a better understanding of the mechanism of the lytic action of Pseudomonas spp. against V. harveyi, which eventually lead to possible measure to control V. harveyi infection in shrimp hatchery and pond systems.